PRESPEKTIF ISLAM DALAM STRATEGI PEMBELAJARAN - Ika Permata Bunda; Annisa Rahmah; Gusmaneli Gusmaneli (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Learning strategies as one of the most important components of education are also changing. The learning strategy that is currently required is a learning strategy that is centered on student activities (student centric) in an atmosphere that is more democratic, fair, humane, empowering, fun, exciting, encouraging, arouses interest in learning, stimulates inspiration, imagination, creation, innovation, work ethic, and zest for life. In this way, all human potential can be explored and actualized in life, which in turn can help him to face the various challenges of life in the modern era which is full of competition. This kind of learning strategy is what is needed now. Islamic perspective in learning strategies. Learning strategy is a systematic plan to achieve learning goals. In Islam, there are several principles that can be applied in developing learning strategies so that they are in line with Islamic values